2018
DOI: 10.1039/c8qm00382c
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the positions of CH⋯N in acceptors of pyrimidine–pyridine hybrids for highly efficient sky-blue thermally activated delayed fluorescent OLEDs

Abstract: Manipulating the positions of CH⋯N in acceptors along the orientation of the electron cloud distributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…Organic materials with extended π-conjugation along their backbone have been intensively studied because of their applications in a wide range of electronic and optoelectronic devices . Among π-conjugated systems, push–pull molecules (D–A), constituted of a conjugated π-electron system asymmetrically substituted by an electron-donor group (D) and an electron-withdrawing one (A), as well as molecules with donor–acceptor–donor (D–A–D) architecture have been widely investigated to construct organic low-band gap materials for optoelectronic devices, such as organic light-emitting diodes (OLEDs), organic photovoltaic cells (OPVs) and organic solar cells, organic field-effect transistors, nonlinear optics (NLO), and fluorescent chemosensors …”
Section: Introductionmentioning
confidence: 99%
“…Organic materials with extended π-conjugation along their backbone have been intensively studied because of their applications in a wide range of electronic and optoelectronic devices . Among π-conjugated systems, push–pull molecules (D–A), constituted of a conjugated π-electron system asymmetrically substituted by an electron-donor group (D) and an electron-withdrawing one (A), as well as molecules with donor–acceptor–donor (D–A–D) architecture have been widely investigated to construct organic low-band gap materials for optoelectronic devices, such as organic light-emitting diodes (OLEDs), organic photovoltaic cells (OPVs) and organic solar cells, organic field-effect transistors, nonlinear optics (NLO), and fluorescent chemosensors …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the intramolecular hydrogen bonding between the nitrogen in pyridine ring of phenyl­(pyridyl)­methanone and the adjacent C–H bonds of the carbazole group with a distance of 2.52 Å in 3CPyM-PXZ was observed. The existence of intramolecular hydrogen bonding was expected to restrict the intramolecular rotation, which will increase the PLQY in the solid state and increase the molecular stability. , Moreover, the similar intramolecular hydrogen bonding was not found in the single crystals of CBM-DMAC and CBM-PXZ. For other compounds, even though the crystal structures were not obtained, the existence of similar hydrogen bonding from the DFT optimization could be predicted.…”
Section: Resultsmentioning
confidence: 99%
“…The melting point ( T m ) of PyDCz and PymDCz is as high as 229 and 258 °C (Table ), respectively. These results indicate that the thermal properties are enhanced by the introduction of additional nonbonding CH···N interactions, suggesting their promising potential in the thermally evaporated device fabrications …”
Section: Results and Discussionmentioning
confidence: 99%
“…Here, we introduce NCIs into the host materials of blue PhOLEDs in D-A-D molecular architectures to explore the effect of the NCIs on the electrical performance of organic semiconductors. Carbazole with sufficiently high triplet energy and good hole-transporting ability was selected as the donor unit, and the strong electron-deficient nitrogen six-membered heterocyclic rings of pyridine, pyrimidine, and pyrazine were used as the accepters to construct three new D-A-D host molecules with noncovalent intramolecular CH···N interactions. , These host molecules with high E T were facilely prepared through a one-step C–N coupling reaction in high yields . Combined computational and experimental investigations showed that the intramolecular CH···N interactions can successfully tune the molecular conformation and modulate their corresponding packing modes in solid states.…”
Section: Introductionmentioning
confidence: 99%